Α‐Mangostin attenuates stemness and enhances cisplatin‐induced cell death in cervical cancer stem‐like cells through induction of mitochondrial‐mediated apoptosis. Issue 7 (20th January 2020) - Chien, Hung‐Ju; Ying, Tsung‐Ho; Hsieh, Shu‐Ching; Lin, Chia‐Liang; Yu, Yung‐Luen; Kao, Shao‐Hsuan; Hsieh, Yi‐Hsien
Abstract: Cancer stem cells (CSCs) exhibit specific characteristics including decontrolled self‐renewal, tumor‐initiating, promoting, and metastatic potential, abnormal stemness signaling, and chemotherapy resistance. Thus, targeting CSC is becoming an emerging cancer treatment. α‐Mangostin has been shown to have potent and multiple anticancer activities. Accordingly, we hypothesized that α‐mangostin may diminish the stemness and proliferation of CSC‐like cervical cancer cells. In our results, comparing to the parent cells, CSC‐like SiHa and HeLa cells highly expressed CSC marker Sox2, Oct4, Nanog, CK‐17, and CD49f. α‐Mangostin significantly reduced the cell viability, sphere‐forming ability, and expression of the CSC stemness makers of CSC‐like cervical cancer cells. Further investigation showed that α‐mangostin induced mitochondrial depolarization and mitochondrial apoptosis signaling, including upregulation of Bax, downregulation of Mcl‐1 and Bcl‐2, and activation of caspase‐9/3. Moreover, α‐mangostin synergically enhanced the cytotoxicity of cisplatin on CSC‐like SiHa cells by promoting mitochondrial apoptosis and inhibiting the expression of CSC markers. Consistent with in vitro findings, in vivo tumor growth assay revealed that α‐mangostin administration significantly inhibited the growth of inoculated CSC‐like SiHa cells and synergically enhanced the antitumor effect of cisplatin. Our findings indicate that α‐mangostin can reduce the stemness and proliferation of CSC‐like SiHa and HeLa cells and promote the cytotoxicity of cisplatin, which may attribute to the mitochondrial apoptosis activation. Thus, it suggests that α‐mangostin may have clinical potential to improve chemotherapy for cervical cancer by targeting cervical CSC. Abstract : α‐Mangostin synergistically enhances the cisplatin on cancer stem cell‐like cervical cancer cells via inducing mitochondrial apoptosis.